PERAN GURU PAI DAN BUDI PEKERTI DALAM MENINGKATKAN KEAKTIFAN SISWA MELALUI PEMBELAJARAN BERBASIS CANVA DI SMP IT TAQIYYA ROSYIDA KARTASURA TAHUN AJARAN 2025/2026 - Diah Novita Fardani; Putri Dwi Watantri (STKIP Subang, 2026)
This study was motivated by the growing demand for technology-based learning in the digital era, requiring teachers to integrate technology, pedagogy, and content knowledge (TPACK) into the learning process. SMP IT Taqiyya Rosyida Kartasura implements Canva-based learning in Islamic Religious Education and Character Education classes to enhance student activeness. This study aimed to describe the role of teachers in improving student activeness through Canva-based learning and to identify its supporting and inhibiting factors. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings showed that teachers acted as guides, facilitators, motivators, innovators, and role models in implementing Canva-based learning. Student activeness increased in asking and answering questions, participating in discussions, and completing assignments. Supporting factors included student enthusiasm, teacher creativity, and adequate facilities, while inhibiting factors involved limited devices, internet connectivity issues, and differences in students’ technological abilities.